Jawel, ik zing terwijl ik inadem! - Vanhecke, Françoise; Moerbeke, Katrien van (Oostkamp Stichting Kunstboek, 2025)
Over a decade ago, Françoise Vanhecke discovered and developed a new singing technique “Inhaling Singing” or ISFV® (Inhaling Singing by Françoise Vanhecke®) for short.In her recently published book “ JAWEL, IK ZING TERWIJL IK INADEM” Vanhecke explains in an accessible way the discovery, development and peculiarities of this unique singing technique. This book casts a wider perspective on contemporary singing technique, on modern music and stimulates an intense musical experience, helping the reader to discover the uniqueness of ISFV® and to distinguish this technique from other extended vocal techniques so that they quickly discover why this technique is an added value to the vocal idiom. More than thirty artistic realizations with ISFV® are described as to why and how the technique was applied in the performances concerned. The book is richly illustrated with action photos and provided with audio fragments linked by QR codes, including works by Flemish composers. (Translated with DeepL.com)
Keywords: Voice; Singing; Extended technique